Muscle-fiber typology is associated with sprint-cycling characteristics in world-class and elite track cyclists - Wackwitz, T.; Minahan, C.; Lievens, E.; Kennedy, B.; Derave, W.; Bellinger, P. (International Journal of Sports Physiology and Performance, 2025)
Purpose Identifying the determinants of performance is fundamental to talent identification and individualizing training prescription. Consequently, the aim of this study was to determine whether estimated muscle typology is associated with the key mechanical characteristics of track sprint cycling.